Kinerja Guru dan Problematika Mutu Pendidikan Agama Islam di Indonesia - Juliawan, Abdul Azis (Tsamratul Fikri | Jurnal Studi Islam, 2021)
Quality education is one of the goals of learning in Indonesia. Quality education will not be realized if the supporting factors do not run according to their function. Teachers as educators have a central role in realizing this quality education. However, several obstacles arise that cause the teacher's performance to be less than optimal. Not only general education, Islamic religious education also gets the spotlight on the quality of education that is still lacking and the problems it faces. This study aims to examine the performance of Islamic religious education teachers and the problems of the quality of Islamic religious education that have emerged until now. This study uses the literature review method or literature review. Sources of data were obtained from various reference books and scientific journals. Then the data is collected and analyzed in depth. From this study, it was found that the performance of PAI teachers was still less than optimal, this happened because of the lack of teacher discipline in punctuality and obeying school rules, as well as the lack of teachers mastering the ability to plan learning tools. Furthermore, the problem of the quality of Islamic religious education arises based on several factors, both educators, students, curriculum, management and facilities, and infrastructure.